2006
DOI: 10.1007/11818175_24
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotically Optimal Two-Round Perfectly Secure Message Transmission

Abstract: Abstract. The problem of perfectly secure message transmission concerns two synchronized non-faulty processors sender (S) and receiver (R) that are connected by a synchronous network of n ≥ 2t + 1 noiseless 2-way communication channels. Their goal is to communicate privately and reliably, despite the presence of an adversary that may actively corrupt at most t of those channels. These properties should hold information theoretically and without error. We propose an asymptotically optimal solution for this prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 6 publications
0
53
0
Order By: Relevance
“…The goal is to send the message both privately and reliably. Since its introduction, SMT has been widely studied and optimized with respect to several different settings of parameters (for example, see [SA96,SNP04,ACH06,FFGV07,KS08]). …”
Section: Introductionmentioning
confidence: 99%
“…The goal is to send the message both privately and reliably. Since its introduction, SMT has been widely studied and optimized with respect to several different settings of parameters (for example, see [SA96,SNP04,ACH06,FFGV07,KS08]). …”
Section: Introductionmentioning
confidence: 99%
“…More recently, Srinathan, Narayanan and Rangan [18] showed that, in order to achieve two-round PSMT, Ω(n ) bits must be communicated. This lower bound has been matched by the protocol by Agarwal, Cramer and de Haan [1], at the price, however, of requiring messages of length exponential in n. In [16], Patra, Choudhary, Srinathan and Rangan show that by using one additional round (i.e., three rounds in total), this communication bound can be achieved with polynomial message length.…”
Section: Introductionmentioning
confidence: 95%
“…Let Π 2 be the communication-optimal (but inefficient) two-round PSMT protocol in [1] (or even the communication-suboptimal protocol in [17]) for ν wires tolerating τ = ν−1 2 corrupted wires, where ν = O(1) (ν will be quantified later, based on the analysis below). Choosing ν = O(1) implies that protocol Π 2 's communication overhead is constant, and thus that Π 2 is communication-optimal.…”
Section: The Wire Virtualization Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also already mentioned the relation of our tool for secure channels to the problem of perfectly secure message transmission [10], which has been further studied in, e.g., [28,8,29,1,12,24]. In [15], Franklin and Wright take a different approach and study the necessary and sufficient conditions for secure message transmissions over multicast lines.…”
Section: Introductionmentioning
confidence: 99%